Hyperbaric Oxygen Therapy Can Induce Neuroplasticity and Significant Clinical Improvement in Patients Suffering From Fibromyalgia With a History of Childhood Sexual Abuse—Randomized Controlled Trial - Hadanny, Amir; Bechor, Yair; Catalogna, Merav; Daphna–Tekoah, Shir; Sigal, Tal; Cohenpour, Mehrzad; Lev-Wiesel, Rachel; Efrati, Shai (Frontiers in Psychology, 2018)
1. Abstract 1.1 Background Fibromyalgia syndrome (FMS), a condition considered to represent a prototype of central sensitization syndrome, can be induced by different triggers including childhood sexual abuse (CSA). Recent studies have demonstrated hyperbaric oxygen therapy (HBOT) can induce neuroplasticity and improve clinical outcome of FMS. The aim of the current study was to evaluate the effect of HBOT on patients suffering from FMS due to CSA. 1.2 Materials and methods A prospective randomized clinical trial conducted between July 2015 and November 2017 included women with a history of CSA who fulfilled fibromyalgia diagnosis criteria for at least five years prior to inclusion. Included participants (N=30) were randomly assigned to treatment group, treated with 60 HBOT sessions and a control/crossover group received psychotherapy. After the control period, the control/crossover group was crossed to HBOT. Clinical outcome included FMS, PTSD and quality of life questioners and brain function and structure imaging. 1.3 Findings Following HBOT, there was a significant improvement in all FMS questionnaires (WPI, SSS, FIQ), most domains of quality of life (SF-36) and PTSD questionnaires (BSI, PSS). The same significant improvements were demonstrated in the control following crossover to HBOT. Following HBOT, brain SPECT imaging demonstrated significant increase in brain activity in the prefrontal cortex, orbital frontal cortex and subgenual area (p<0.05). Brain microstructure improvement was seen by MRI-DTI in the anterior thalamic radiation (p=0.0001), left Insula (p=0.001) and the right Thalamus (p=0.001). 1.4 Conclusion HBOT induced significant clinical improvement that correlates with improved brain functionality and brain microstructure in CSA related FMS patients. Trial registration: Clinicaltrials.gov, trial ID: NCT03376269 url: https://clinicaltrials.gov/show/NCT03376269